Node of Ranvier disruption as a cause of neurological diseases - Susuki, Keiichiro (American Society for Neurochemistry, 2013)
Dysfunction and/or disruption of nodes of Ranvier are now recognized as key contributors to the pathophysiology of various neurological diseases. One reason is that the excitable nodal axolemma contains a high density of Nav (voltage-gated Na(+) channels) that are required for the rapid and efficient saltatory conduction of action potentials. Nodal physiology is disturbed by altered function, localization, and expression of voltage-gated ion channels clustered at nodes and juxtaparanodes, and by disrupted axon–glial interactions at paranodes. This paper reviews recent discoveries in molecular/cellular neuroscience, genetics, immunology, and neurology that highlight the critical roles of nodes of Ranvier in health and disease.